2016
DOI: 10.1007/s00787-016-0908-4
|View full text |Cite
|
Sign up to set email alerts
|

Can psychiatric childhood disorders be due to inborn errors of metabolism?

Abstract: Many patients who visit a centre for hereditary metabolic diseases remarkably also suffer from a child psychiatric disorder. Those child psychiatric disorders may be the first sign or manifestation of an underlying metabolic disorder. Lack of knowledge of metabolic disorders in child psychiatry may lead to diagnoses being missed. Patients therefore are also at risk for not accessing efficacious treatment and proper counselling. To search the literature for the co-occurrence of child psychiatric disorders, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Metabolic diseases most associated with ADHD are succinic semialdehyde dehydrogenase deficiency, phenylketonuria, X-linked ichthyosis, and mucopolysaccharidosis type III (Sanfilippo syndrome). 11 Establishing a genotype-phenotype correlation in tyrosinemia is difficult since the literature has very few cases described on the subject, and only some of them identify distinct mutations. Tables 1 and 2 summarize the main clinical and analytical characteristics of patients known to date.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic diseases most associated with ADHD are succinic semialdehyde dehydrogenase deficiency, phenylketonuria, X-linked ichthyosis, and mucopolysaccharidosis type III (Sanfilippo syndrome). 11 Establishing a genotype-phenotype correlation in tyrosinemia is difficult since the literature has very few cases described on the subject, and only some of them identify distinct mutations. Tables 1 and 2 summarize the main clinical and analytical characteristics of patients known to date.…”
Section: Discussionmentioning
confidence: 99%
“…Simons et al reviewed 71 papers for psychiatric childhood disorders secondary to inborn errors of metabolism. They reported ALD to be associated only with learning disorders;5 while Sedel et al reported that psychiatric symptoms like mania, depression and acute psychosis may precede motor symptoms in late onset ALD 6. Ray et al presented a 15-year old with ALD presenting as treatment resistant mania 7.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health disorders can occur in patients with IEM disorders due to accumulation of neurotoxic compounds in the central nervous system, through enzymatic defects, or other protein dysfunction; causing disruption of neurodevelopmental processes or impact on neurotransmitter systems (23). These disorders vary in presentation from psychiatric emergencies, including A caveat in the management of psychiatric disorders cooccurring in patients with IEM is that some of the symptoms may become "treatment-resistant" as the underpinning neurobiology differs from the primary psychiatric illness.…”
Section: Psychiatric Disorders and Iemmentioning
confidence: 99%